Protective effect of melatonin against ischemia/reperfusion-induced oxidative remote organ injury in the rat - ŞENER, GÖKSEL (SPRINGER, 2005)
Purpose. Oxygen free radicals are considered to be important components involved in the pathophysiological tissue alterations observed during ischemia/reperfusion (I/R). Based on the potent antioxidant effects of melatonin, we investigated the putative protective role of melatonin against I/R-induced oxidative remote organ injury. Methods. Wistar albino rats were subjected to 1 h of infrarenal aortic occlusion followed by 1 h of reperfusion to induce I/R damage. Melatonin (10 mg/kg, s.c.) or vehicle was administered twice, 15 min prior to ischemia and immediately before the reperfusion period (I/R + Mel or I/R groups). At the end of the reperfusion periods, the rats were decapitated and hepatic, ileal, and lung tissue samples were removed for biochemical analyses of: malondialdehyde (MDA), an end product of lipid peroxidation; the glutathione (GSH) levels, a key antioxidant; and the myeloperoxidase (MPO) activity, as an indirect index of neutrophil infiltration. The serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels were measured to evaluate the liver function. The wet/dry lung weight ratio was calculated to determine the extent of lung damage. Results. The results revealed the occurrence of I/R-induced oxidative organ damage, as evidenced by increases in the MDA and MPO activity, and a decrease in GSH. Furthermore the AST, ALT levels, and the wet/dry lung weight ratio, which all increased due to I/R, were all observed to decrease after melationin treatment. Conclusion. Since melatonin administration reversed these oxidant responses, it seems likely that melationin has a protective effect against oxidative organ damage induced by I/R.
Keywords: melatonin; ischemia/reperfusion; lipid peroxidation; glutathione; myeloperoxidase; ISCHEMIA-REPERFUSION INJURY; LIPID-PEROXIDATION; MYELOPEROXIDASE ACTIVITY; RADICAL SCAVENGER; MECHANISMS; GLUTATHIONE; LIVER; ANTIOXIDANT; NEUTROPHILS; TISSUE